Fruit Evaluation of Minor Nubian Date Palm Cultivars (University of Khartoum Journal of Agricultural Sciences, 2023)
Domestication of date palm in the Nuba-land of Mahas andSakkot tribes since ancient times had been well documented inarcheological records. The commercially valuable Sudanese date palmcultivars originated there and were distributed country-wise. Besides,there are many minor cultivars in that habitat, rarely recognized in otherdates producing areas in Sudan. In this study, the physical, chemical andsensory attributes of 10 of these cultivars were studied in comparison toBarakawi, the major date cultivar in Sudan. Kulmat Al Borgaig scored toprank for fruit weight, width and pulp thickness, sharing weight positionwith Kajnosa, while Barakawi fruit was the longest. The highest total andnon-reducing sugars were recorded in Zagloul and Kulumtoad fruits. Themoisture content of all cultivars was extremely low, except for KulmatAlBorgaig which was characterized by relatively higher moisture. Theoverall acceptance in the panel of sensory evaluation was in favour ofKulmat Al Borgaig and Kajnosa, with relatively higher grades for tasteand palatability for Kulmat Al Borgaig.
Keywords: Date palm (Phoenix dactylifera L; Nubian cultivars; Physico-chemical; Sensory